Thrombectomy Technique Predicts Outcome in Posterior Circulation Stroke—Insights from the STAR Collaboration. Issue 5 (November 2020) - Alawieh, Ali M; Eid, Maya; Anadani, Mohammad; Sattur, Mithun; Maier, Ilko L; Feng, Wuwei; Goyal, Nitin; Starke, Robert M; Rai, Ansaar; Fargen, Kyle M; Psychogios, Marios‐Nikos; De Leacy, Reade; et al.
Abstract : BACKGROUND: : Randomized controlled trials evaluating mechanical thrombectomy (MT) for acute ischemic stroke predominantly studied anterior circulation patients. Both procedural and clinical predictors of outcome in posterior circulation patients have not been evaluated in large cohort studies. OBJECTIVE: : To investigate technical and clinical predictors of functional independence after posterior circulation MT while comparing different frontline thrombectomy techniques. METHODS: : In a retrospective multicenter international study of 3045 patients undergoing MT for stroke between 06/2014 and 12/2018, 345 patients had posterior circulation strokes. MT was performed using aspiration, stent retriever, or combined approach. Functional outcomes were assessed using the 90‐d modified Rankin score dichotomized into good (0‐2) and poor outcomes (3‐6). RESULTS: : We included 2700 patients with anterior circulation and 345 patients with posterior circulation strokes. Posterior patients (age: 60 ± 14, 46% females) presented with mainly basilar occlusion (80%) and were treated using contact aspiration or ADAPT (39%), stent retriever (31%) or combined approach (19%). Compared to anterior strokes, posterior strokes had delayed treatment (500 vs 340 min, P < .001), higher national institute of health stroke scale (NIHSS) (17.1 vs 15.7, P < .01) and lower rates of good outcomes (31% vs 43%, P < .01). In posterior MT, diabetes (OR = 0.28, 95%CI: 0.12‐0.65), admission NIHSS (OR = 0.9, 95%CI: 0.86‐0.94), and use of stent retriever (OR = 0.26, 95%CI: 0.11‐0.62) or combined approach (OR = 0.35, 95%CI: 0.12‐1.01) vs ADAPT were associated with lower odds of good outcome. Stent retriever use was associated with lower odds of good outcomes compared to ADAPT even when including patients with only basilar occlusion or with successful recanalization only. CONCLUSION: : Despite similar safety profiles, use of ADAPT is associated with higher rates of functional independence after posterior circulation thrombectomy compared to stent retriever or combined approach in large "real‐world" retrospective study.